Analysis of Changes in Mangrove Vegetation Area Using The Normalized Difference Vegetation Index Method in The Waters of Bungin Permai, South Konawe - Ardiansyah, M. Ipal; Asmadin; Ira; Ramli, Muhammad; Adimu, Hasan Eldin; Fekri, Latifa; Harimudin, Jamal (Coastal and Marine Journal, 2023)
Changes around mangrove vegetation in Bungin Permai Waters, Tinanggea District, South Konawe Regency over the last 30 years (1992-2022). Aims to analyze changes in mangrove vegetation areas spatially and temporarily. The research method used remote sensing of Landsat 5 TM, 7 ETM +, and Landsat 8 OLI satellite image data and NDVI method to see changes in mangrove vegetation area, reduced mangrove vegetation area by 75% ranging from 767 Ha. Shows that, along with the reduction in mangrove vegetation area can cause an increase in TSS concentration, the potential for sea level rise to settlements, the absence of sedimentation rate retaining media to the high seas, to the loss of mangrove area animal habitat. The area of mangrove vegetation decreases by 75% or around 767 Ha over time.